Organizational strategy, resource management, communication, collaboration, higher education advocacy, professionalism and effective academic leadership styles in Malaysian RUs. - Shahmandi, Elham; Silong, Abu Daud (TextRoad Publication, 2013)
The importance of systematically developing human resources today is highly complex because globalization has had far- reaching implications for human resource development (HRD) through recognizing appropriate competencies for academic leaders. Leaders can be more effective based on leadership behaviors exhibited by academic leaders in the international environment. Leadership scholars have called for additional research on leadership competencies requirements and how those requirements vary according to effective leadership styles. The research question examined in the context of middle level academic leadership. The purpose of this research is to examine the relationship between six leadership competencies (organizational strategy, resource management, communication, collaboration, higher education advocacy, professionalism) and four Effective Academic Leadership Styles (EALS) in the present situation of globalization and academic excellence. The total number of respondents in this study was 183 academic leaders who hold administrative positions in Malaysian RUs. Based on the results using Structural Equation Modeling (SEM), contributions of leadership competencies depend on leadership styles in certain situations. Most of the competencies have a relationship to EALS, except two dimensions that include organizational strategy and communication. Finally, systematic leadership development programs should be developed to ensure that appropriate EALS utilized in RUs.